Cricothyrotomy Is Faster Than Tracheostomy for Emergency Front-of-Neck Airway Access in Dogs - Hardjo, Sureiyan; Croton, Catriona; Woldeyohannes, Solomon; Purcell, Sarah Leonie; Haworth, Mark David (Frontiers in Veterinary Science, 2021)
Objectives: In novice final year veterinary students, we sought to: (1) compare the procedure time between a novel cricothyrotomy (CTT) technique and an abbreviated tracheostomy (TT) technique in canine cadavers, (2) assess the success rate of each procedure, (3) assess the complication rate of each procedure via a damage score, (4) evaluate the technical difficulty of each procedure and (5) determine the preferred procedure of study participants for emergency front-of-neck access. Materials and Methods: A prospective, cross-over, block randomised trial was performed, where veterinary students completed CTT and TT procedures on cadaver dogs. Eight students were recruited and performed 32 procedures on 16 dogs. A generalised estimating equation approach to modelling the procedure times was used. Results: The procedure time was significantly faster for the CTT than the TT technique, on average (p < 0.001). The mean time taken to complete the CTT technique was 49.6 s (95% CI: 29.5–69.6) faster on average, with a mean CTT time of less than half that of the TT. When taking into account the attempt number, the procedure time for a CTT was 66.4 s (95% CI: 38.9–93.9) faster than TT for the first attempt, and for the second attempt, this was 32.7 s (95% CI: 15.2–50.2) faster, on average. The success rate for both procedures was 100% and there was no difference detected in the damage or difficulty scores (P = 0.13 and 0.08, respectively). Seven of eight participants preferred the CTT. Clinical Significance: CTT warrants consideration as the primary option for emergency front-of-neck airway access for dogs.